Ningen jōhatsu : A man vanishes - Imamura, Shōhei, 1926-2006; Imamura, Shōhei, 1926-2006; Imamura, Shōhei, 1926-2006; Urayama, Kirio, 1930-1985; Tsuyuguchi, Shigeru; Hayakawa, Yoshie; Hayakawa, Sayo (Icarus Films, 2012)
"The film follows the case of Tadashi, a handsome businessman who has suddenly vanished. Imamura and his crew interview the man's fiancée, Yoshie, who is desperately searching for him, and the filmmaker becomes increasingly involved in her life. But the 'investigation' casts a shadow of doubt over the couple's relationship, Tadashi's business ventures, his relationship with Yoshie's sister, and even the investigating film director, Imamura himself, who may not be what he seems. Radical film in scope, technique, and aesthetic, A man vanishes distills many of Imamura's central themes and obsessions, the film culminating a sequence that explodes any stable sense of fiction and reality."--Publisher's webside.